2013
DOI: 10.1177/1533317513504612
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mild Cognitive Impairment on Sexual Activity

Abstract: Findings from the present study support the significant role of cognitive functioning to perform sexual activity in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…These potential sociodemographic factors included age, sex, marital status, educational attainment, ethnicity, and stratum (place of residence). 15 , 20 …”
Section: Methodsmentioning
confidence: 99%
“…These potential sociodemographic factors included age, sex, marital status, educational attainment, ethnicity, and stratum (place of residence). 15 , 20 …”
Section: Methodsmentioning
confidence: 99%
“…Sexual activity is equivalent to mild to moderate physical activity in the range of 3–5 METS (metabolic equivalents) [ 7 ], but very little research has focussed specifically on possible associations between sexual activity and cognitive function. The limited amount of existing research focuses on of the impact of cognitive impairment or dementia on sexual relationships in older adult couples [ 8 10 ]. A recent systematic review found that those experiencing cognitive decline and dementia engaged in fewer sexual activities than their cognitively intact, non-demented counterparts [ 11 ].…”
mentioning
confidence: 99%
“…Relevance for erectile function. The cognitive defects and sleep disorders featured in long COVID 70 contribute to poorer sexual health 71 , 72 , 73 . Likewise, chronic fatigue has been associated with declining sexual functioning 74 .…”
Section: Resultsmentioning
confidence: 99%